2021
DOI: 10.1111/andr.13111
|View full text |Cite
|
Sign up to set email alerts
|

Association between obstructive sleep apnea and male serum testosterone: A systematic review and meta‐analysis

Abstract: Background Currently, there is no consensus on the effect of obstructive sleep apnea on male serum testosterone levels. This systematic review and meta‐analysis aimed to determine the association between obstructive sleep apnea and male serum testosterone level. Methods The literature related to obstructive sleep apnea and male serum testosterone in the PubMed, Embase, and Cochrane Library databases were searched from their inception to June 10, 2021. Data were pooled using the Stata 15 software. We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
(186 reference statements)
0
9
0
Order By: Relevance
“…OSA is also associated with reduction in serum testosterone concentration, with the most recent meta‐analysis indicating that this change is beyond the effect of underlying obesity 150 . Currently, there is limited evidence that continuous positive airway pressure (CPAP) therapy results in improvement in serum testosterone concentrations, 151 although this meta‐analysis assessed only 388 men with obesity‐related comorbidities, and appropriate use of CPAP was not assessed.…”
Section: Why There May Be Descrepancies As To the Effect Of Obesity O...mentioning
confidence: 99%
“…OSA is also associated with reduction in serum testosterone concentration, with the most recent meta‐analysis indicating that this change is beyond the effect of underlying obesity 150 . Currently, there is limited evidence that continuous positive airway pressure (CPAP) therapy results in improvement in serum testosterone concentrations, 151 although this meta‐analysis assessed only 388 men with obesity‐related comorbidities, and appropriate use of CPAP was not assessed.…”
Section: Why There May Be Descrepancies As To the Effect Of Obesity O...mentioning
confidence: 99%
“…To address this controversy, 2 recent meta-analyses abstracted data from case-control studies and confirmed the association between OSA and low testosterone, even after controlling for comorbid conditions. 8,9 However, another meta-analysis failed to demonstrate any improvements in testosterone after treating OSA, arguing against a causative role. 10 Although treating OSA may not improve testosterone levels, initiating testosterone therapy in men with OSA may lead to a worsening of symptoms.…”
Section: Osamentioning
confidence: 99%
“…This association may [ 37 ] or may not [ 104 106 ] be due to obesity. A recent meta-analysis of 18 studies involving 1823 men with or without OSA also found a significant inverse relationship between OSA and testosterone concentrations – a relationship which remained after controlling for age and obesity [ 107 ]. Notably, a significantly lower testosterone was only observed in men with severe OSA.…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%